The Punjab peasant in prosperity and debt - Darling, Malcolm (London ; New York : Oxford University Press, 1928)
On land tenure and economic conditions in Punjab.
Master microform held by: ICRL.
0
Keywords: Land tenure -- India -- Punjab; MCE; Peasants -- India -- Punjab